Online Formative Assessment in Mathematics Education: Prospective Primary Teachers’ Understanding of Rational Numbers - Putra, Zetra Hainul; Sari, Intan Kartika; Dahnilsyah, Dahnilsyah (Revija za elementarno izobraževanje, 2023)
This study sheds light on prospective primary teachers’ understanding of rational numbers. This is an experimental study that aims to evaluate prospective primary teachers’ mathematical and didactic knowledge of rational numbers through online formative assessment. The participants were 38 prospective primary teachers from a primary teacher education study program at a public university in Pekanbaru, Riau, Indonesia. This study indicates that the prospective teachers have insufficient knowledge of rational numbers, and they possess better mathematical than didactic knowledge. This study also reveals a significant increase in prospective teachers’ mathematical and didactic scores from the first test to the second test.